1999
DOI: 10.1021/jp991870+
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Induced Dynamics of a Benzylic Amide [2]Catenane

Abstract: The electrochemistry of a benzylic amide [2]catenane was investigated and compared to that of its topologically trivial components. The redox behavior of both the catenane and the uninterlocked macrocycle can be largely understood in terms of the electrochemistry of smaller molecular fragments and simple molecular orbital considerations that show that the electroactivity of the CO groups is split into two sets of quasi-degenerate potentials separated by a substantial gap. A fast intermolecular reaction follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…For example, photoisomerization of an azobenzene unit in a π‐donor/acceptor [2]catenane was found to influence the rate of dynamic processes, presumably by altering the size of the macrocycle cavity 263. Electrochemical reduction of a homocircuit benzylic amide [2]catenane completely halts the circumrotational process as a result of the formation of an intercomponent covalent bond between the macrocycles 264. Protonation of a porphyrin free base in a catenane was found to result in a rearrangement to minimize repulsive electrostatic interactions, thus altering the rate of pirouetting of a tetracationic cyclophane 191w.…”
Section: Controlling Motion In Mechanically Bonded Molecular Systemsmentioning
confidence: 99%
“…For example, photoisomerization of an azobenzene unit in a π‐donor/acceptor [2]catenane was found to influence the rate of dynamic processes, presumably by altering the size of the macrocycle cavity 263. Electrochemical reduction of a homocircuit benzylic amide [2]catenane completely halts the circumrotational process as a result of the formation of an intercomponent covalent bond between the macrocycles 264. Protonation of a porphyrin free base in a catenane was found to result in a rearrangement to minimize repulsive electrostatic interactions, thus altering the rate of pirouetting of a tetracationic cyclophane 191w.…”
Section: Controlling Motion In Mechanically Bonded Molecular Systemsmentioning
confidence: 99%
“…So beeinflusst die Photoisomerisierung der Azobenzoleinheit in einem π‐Donor‐Acceptor‐[2]Catenan die Geschwindigkeit dynamischer Prozesse, vermutlich durch die Veränderung der Hohlraumgröße des Makrocyclus 263. Die elektrochemische Reduktion eines Benzylamid‐[2]Catenans mit zwei identischen Ringen knüpft eine kovalente Bindung zwischen den Makrocyclen und bringt den Rotationsvorgang daher zum Stillstand 264. Nach der Protonierung der freien Base eines Catenans tritt eine Umlagerung ein.…”
Section: Die Steuerung Der Bewegung In Mechanisch Verknüpften Moleunclassified
“…Ceroni et al [52] reported an investigation of the electrochemistry of a benzylic amide [2]catenane and its topological subcomponents. They proposed that the redox behavior of the catenane could be understood in terms of the electrochemistry of smaller molecular fragments and simple molecular orbital considerations.…”
Section: Dynamics Of Catenane Systemsmentioning
confidence: 99%